2019
DOI: 10.1021/acssuschemeng.9b04327
|View full text |Cite
|
Sign up to set email alerts
|

In Situ ZnO-Activated Hierarchical Porous Carbon Nanofibers as Self-Standing Electrodes for Flexible Zn–Air Batteries

Abstract: With the advantages of low cost, non-pollution, and strong controllability over composition, morphology, nanostructures, as well as surface characters, carbon-based nanomaterials are regarded as ideal substitutes of traditional platinum-based catalysts for oxygen reduction reaction (ORR) electrocatalysis in ORR-involved devices. Herein, an in situ ZnO activation-coupled electrospinning strategy was employed to facilely construct nitrogen-doped porous carbon nanofibers (NPCNF) for flexible Zn−air batteries. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…Recently, ZnO was introduced in electrospinning to promote the formation of hierarchical porous structure nanofibers (Figure 7e). [ 71 ] The NPCNFs can be used as a binder‐free self‐standing air cathode in the flexible solid‐state primary ZAB (Figure 7f).…”
Section: Electrospinning In Zabsmentioning
confidence: 99%
“…Recently, ZnO was introduced in electrospinning to promote the formation of hierarchical porous structure nanofibers (Figure 7e). [ 71 ] The NPCNFs can be used as a binder‐free self‐standing air cathode in the flexible solid‐state primary ZAB (Figure 7f).…”
Section: Electrospinning In Zabsmentioning
confidence: 99%
“…Yan et al studied an in situ ZnO‐activation‐coupled electrospinning strategy to facilely construct nitrogen‐doped porous CNFs (NPCNF) applied in Zn–air batteries (ZABs). [ 74 ] After ZnO in situ immobilization and thermal removal, micro/mesoporous structures with specific surface area at 501 m 2 g −1 ( Figure 7 b) and highly active N‐doped sites with 5.6 at% exist in the nanofibers. As a result, NPCNF exhibits a 0.85 V half‐wave potential and the power density of ZABs at 84.02 mW cm −2 .…”
Section: Electrospinning Fibers In Orr Catalysismentioning
confidence: 99%
“…Because a considerable over-potential of the ORR is required to overcome the energy barriers associated with multi-step electron transfer [ 10 ], the main challenge faced in developing flexible rechargeable ZABs that can be applied on a large scale is the use of air cathodes in the ZABs that exhibit excessive potential [ 11 ] and poor oxygen reversibility caused by the slow ORR and OER during charge and discharge [ 12 ]. The Pt/C electrodes demonstrate the best catalytic performance for the ORR, whereas IrO 2 /RuO 2 demonstrates an excellent catalytic performance in the OER.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been shown that the Co-N x sites and the N embedded in the carbon matrix are active sites in non-noble metal ORR hybrid catalysts [ 68 ]. Other examples include transition metals (Co and Fe) on N-doped carbon [ 39 , 71 , 72 ], pyridine-N [ 58 ], graphitization-N [ 71 ], Co-azo species [ 71 ], N, P co-doped materials, layered N-doped heteroporous carbon nanofibers that possess excellent electron transport paths and a high specific surface area [ 10 ] and graphene nanocomposites. Graphene nanocomposites have been synthesized through the in situ hydrothermal growth of CoSe and nickel selenide nanoparticles on graphene nanosheets (GNs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation